Towards a socially sustainable world economy : an analysis of the social pillars of globalization Raymond Torres.. - Torres, Raymond. (Studies on the social dimensions of globalization, 2001)
"Presenting new analytical and policy-oriented research, this timely study examines the positive and negative social effects of globalization in countries at various stages of economic development. It looks at how globalization stimulates output and income, but can also create wider income inequalities, job instability and economic vulnerability. It investigates what kinds of policies (economic, social and labour) can be adopted to improve the benefits and reduce the costs as the world becomes more economically integrated." "Using statistical evidence and analytical tools, the book examines in depth the social impact in Bangladesh, Chile, Mauritius, Poland, the Republic of Korea, South Africa and Switzerland. It takes an objective approach to understanding the relationship between social progress and various dimensions of globalization, including trade liberalization, foreign direct investment and free capital movements." "The study shows that, in contrast to a widely held view that countries are powerless in the face of globalization, governments and the social partners must and can do something. It advocates a strengthening of the social pillars of the globalization process, in areas such as education and training policies, social safety nets, labour law and industrial relations, and core labour standards." "Accompanying this synthesis study are the seven detailed country reports, which can be purchased separately."--BOOK JACKET.